Immediate restoration of fixed full-arch prostheses placed on implants in both fresh and healed sockets using the flat one-bridge technique: a 7-year retrospective study - Simone Marconcini; Enrica Giammarinaro; Ugo Covani; Andrea Mascolo; Guerino Caso; Marco Del Corso (BMC, 2021)
Abstract Background The aim of this retrospective study was to document the long-term clinical efficacy of a surgical-prosthetic technique (the flat one-bridge technique) involving the immediate restoration of both postextraction and nonpostextraction implants supporting full-arch restorations. Methods Implants were placed by adapting the axis to the available bone. Flat definitive abutments were connected during surgery and never disconnected to compensate for eventual implant disparallelism. Bone grafting was performed when needed. The patients received a screw-retained provisional restoration within 48 h of surgery and a final screw-retained prosthesis within 1 year. Results Sixty-six patients received 494 implants distributed in 75 prostheses. The median follow-up was 86 months (range 82-168 months). Only three implants had failed at the last follow-up. Implant survival was 99.6%. Conclusion The flat one-bridge prosthetic protocol is a viable procedure with excellent long-term outcomes. No difference in clinical success could be observed between postextractive and nonpostextractive implants.